Mediatization in Times of Pandemic: How German Grassroots Sports Clubs Employed Digital Media to Overcome Communication Challenges During COVID-19. (September 2022) - Schallhorn, Christiana; Nölleke, Daniel; Sinner, Philip; Seeger, Christof; Nieland, Jörg-Uwe; Horky, Thomas; Mehler, Katja
The COVID-19 pandemic has had a major impact on all societal domains, including sports. Social distancing measures and the closure of sports facilities posed especially severe challenges for grassroots sports clubs, which thrive on joint activities and member social contact. Drawing on mediatization theory, the study examines the communication challenges faced by grassroots sports clubs and the perceived potential of digital media to overcome these obstacles during and beyond the pandemic. Based on in-depth interviews with 32 club officials of German grassroots sports clubs, the study identified ongoing uncertainty about COVID-19 regulations, preserving members' sense of belonging during social distancing, and involving everyone in formal processes as the major communication challenges. While most of the interviewees valued the potential of digital media to address these challenges, they acknowledged that the benefits of digital media for individual members would depend on their skill, motivation, and concerns, as well as on the availability of digital infrastructure. For that reason, digital media were not considered a substitute for face-to-face social contact or sporting activity but were seen to extend opportunities for communication and training. More generally, these findings raise new questions about the relationship between mediatization and social cohesion.